The Reclamation of a Municipal Waste Landfill - Grudziądz Case Study - Majewski, Kamil Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Municipal landfills are one of the most human-transformed areas of nature, and the process of designing and building a landfill is one of the most difficult strategic issues within human clusters, in particular due to the requirements that a landfill should meet, including the method of its establishment and closure. The main aim of the article is to present a case study of one, currently reclaimed landfill, located in Grudziądz - a district town in the Kujawsko-Pomorskie Province - at Rataja Street, which was closed down in 1997.
Keywords: landfill; reclamation; Grudziądz; biogas recovery; wysypisko śmieci; regeneracja; odzysk biogazu